A narrative review on do’s and don’ts in prescription label writing – lessons for pharmacists - Samaranayake NR; Bandara WGRSK; Manchanayake CMGA (Dove Medical Press, 2018)
Nithushi R Samaranayake,1 Wasana GRSK Bandara,2 Chinthana MGA Manchanayake2 1Department of Allied Health Sciences, Faculty of Medical Sciences, University of Sri Jayewardenepura, Nugegoda, Sri Lanka; 2Colombo South Teaching Hospital, Kalubowila, Dehiwala, Sri Lanka Abstract: Providing medicines information is a key role of a pharmacist. Miscommunication between pharmacist and patient may lead to adverse drug events or therapeutic failure. The aim of the review was to summarize the available research findings on factors that lead to poor communication between pharmacist and patient when providing written medicines information on dispensing and auxiliary labels and identify successful interventional approaches that help to alleviate these concerns. We selected articles available on PubMed, SAGE, and Google Scholar databases that are relevant to our objective. A total of 33 articles that matched the objectives of this review were retrieved and evaluated by all three authors. It was found that patient literacy levels, number of medicines dispensed, format and organization of the label, complexity of dosing instructions, precision of writing dosing instructions and use of icons, graphics and pictograms were aspects that were frequently used, and hence assessed by research groups on medicine label writing. Most studies reported that simple and straight forward instructions written legibly were better comprehended by patients. Based on our findings, we provide here useful tips for pharmacists on writing dosing instructions for patients. Finally, we spotlight crucial research gaps related to communicating written dosing instructions that need to be addressed in the future. Keywords: dispensing labels, readability, comprehensibility, dosing instructions, medication safety